Pharmacognostic and Phytochemical Investigation of Stem Bark of Tectona Grandis Linn. - D.V. GOSWAMI; M.J. PATIL; ANUJ MODI; R. TIWARI (International Journal of Pharma and Bio Sciences, 2010)
Bark of Tectona grandis Linn. commonly known as “Sagwan” belongs to the Verbenaceae family and, traditionally used in diabetes, bronchitis, constipation and in various skin ailments. Present work is related to standardization of Tectona grandis by using pharmacognostic (macroscopy, microscopy and physical constants) and phytochemical investigation on stem bark of Tectona grandis. All the parameters were studied according to the WHO and pharmacopoeial guidelines to standardize the Tectona grandis.